The Inequality Possibility Frontier : Extensions and New Applications - Milanovic, Branko (World Bank, Washington, DC, 2013)
This paper extends the Inequality Possibility Frontier approach in two methodological directions. It allows the social minimum to increase with the average income of a society, and it derives all the Inequality Possibility Frontier statistics for two other inequality measures besides the Gini. Finally, it applies the framework to contemporary data, showing that the inequality extraction ratio can be used in the empirical analysis of post-1960 civil conflict around the world. The duration of conflict and the casualty rate are positively associated with the inequality extraction ratio, that is, with the extent to which elite pushes the actual inequality closer to its maximum level. Inequality, albeit slightly reformulated, is thus shown to play a role in explaining civil conflict.